Learning, Absorptive Capacity and Competence at the Individual Level in the Activities of Loading and Unloading of Fuels - Arruda de Araújo, Davi Lucas; Martins Pantuffi, Cláudia; Coti-Zelati, Paolo Edoardo; Popadiuk, Silvio (Revista Administração em Diálogo, 2024)
The aim of this research was to understand how absorptive capacity promotes individual learning and the competences development of drivers that providing service to BR Distributor e Industrial Port Complex of Suape/PE. In the methodological procedures a qualitative research of the exploratory and descriptive type was adopted. Four research subjects were interviewed, including two drivers and two professionals responsible for training and monitoring in loading and unloading processes. Content analysis was used to compare the responses of the informants according to the categories a priori of the theoretical reference. The results revealed two fields of vision: the technician represented by the instructor and operations technician and the operational field, represented by the drivers. With this, it was possible to initially point out some points that were not convergent, such as training hours, flexibility of days, need for recycling and infrastructure to carry out activities, which connotes the need for more effective feedback evaluation tools, focus even on the program taught.